Protective effects of cariporide on endothelial dysfunction induced by high glucose - WANG Shuang-xi; XIONG Xiao-ming; SONG Tao; LIU Li-ying (Acta Pharmacologica Sinica, 2016)
Aim: To explore the effects of cariporide, a selective sodium-hydrogen antiporter inhibitor, on endothelial dysfunction induced by high glucose. Methods: Acetylcholine (ACh)-induced endothelium-dependent relaxation (EDR), sodium nitroprusside (SNP)-induced endothelium-independent relaxation and biochemical parameters including malondialdehyde (MDA), superoxide dismutase (SOD), and nitric oxide (NO) were measured in rat isolated aorta. Results: A 6-h incubation of aortic rings with high glucose (44 mmol/L) resulted in a significant inhibition of EDR, but had no effects on endothelium-independent relaxation. After the 6-h incubation of aortic rings in the co-presence of cariporide (0.01, 0.1, and 1 μmol/L) with high glucose, cariporide prevented the inhibition of EDR caused by high glucose in concentration-dependent manners. Similarly, high glucose decreased SOD activity and contents of NO, and increased MDA concentration in aortic tissue. Cariporide (1 μmol/L) significantly resisted the decrease of NO content and SOD activity, and elevation of MDA concentration caused by high glucose in aortic tissues. Mannitol (44 mmol/L) or cariporide (1 μmol/L) alone had no effect on EDR, endothelium-independent relaxation and biochemical parameters. Conclusion: Cariporide significantly prevented endothelial dysfunction induced by high glucose. The mechanisms of endothelial dysfunction induced by high glucose may involve the activation of sodium-hydrogen antiporter and the generation of oxygen-free radicals, but it is not related to the change of osmolarity.